2014
DOI: 10.1590/s0100-06832014000500017
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia volatilization from nitrogen fertilizers in no-till wheat and maize in southern Brazil

Abstract: SUMMARYCrop residues on the soil surface of no-till systems can intensify ammonia volatilization from N fertilizers applied to cereal crops. This study assessed the magnitude of N losses through ammonia volatilization from urea applied to no-till winter (wheat) and summer crops (maize) on a Typic Hapludox in the south-central region of Paraná, southern Brazil. In addition, the potential of alternative N sources (urea with urease inhibitor, liquid fertilizer, ammonium nitrate and ammonium sulfate) and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 23 publications
4
21
0
2
Order By: Relevance
“…The amount of ammonia volatilized from the addition of urea to the soil surface in our experiment is in the range found by most studies, which varies from 5 to 25 % (Cantarella et al, 2008;Viero et al, 2014). In extreme conditions, however, these losses may be higher than 40 % (Oliveira et al, 2014).…”
Section: Amount Of Ammonia Volatilizedsupporting
confidence: 62%
See 3 more Smart Citations
“…The amount of ammonia volatilized from the addition of urea to the soil surface in our experiment is in the range found by most studies, which varies from 5 to 25 % (Cantarella et al, 2008;Viero et al, 2014). In extreme conditions, however, these losses may be higher than 40 % (Oliveira et al, 2014).…”
Section: Amount Of Ammonia Volatilizedsupporting
confidence: 62%
“…Tasca et al (2011) found that ammonia volatilization following urea application was 30 % higher at a temperature of 35 °C than at 18 °C. Viero et al (2014) observed ammonia losses following urea application of approximately 5 and 15 % of the N applied for winter and summer crops, respectively. O' Connor and Hendrickson (1987) observed that hydrolysis of urea was completed after 1, 4, 6, 7, and 8 days after soil application Unlike the pattern that occurred with urea, the highest losses of ammonia from treatments with OMF or PL were on the days immediately following soil application, regardless of the presence or absence of urease inhibitor.…”
Section: Peak Of Volatilizationmentioning
confidence: 91%
See 2 more Smart Citations
“…Ammonia volatilization has been extensively studied in different regions of Brazil, where reported NH 3 -N losses range from 5 to 78 % of N applied as urea depending on the particular environmental conditions (Lara Cabezas et al, 1997;Cantarella et al, 2008;Rojas et al, 2012;Soares et al, 2012;Viero et al, 2014;Viero et al, 2015). The addition of a urease inhibitor such as N-(n-butyl) thiophosphoric triamide (NBPT) to urea has proved to be an effective, technically feasible method to reduce NH 3 -N losses from common urea and increase the efficiency of topdressed N fertilization in corn (Cantarella et al, 2008;Soares et al, 2012;Viero et al, 2015).…”
Section: Introductionmentioning
confidence: 99%